Electrical magneto hydrodynamic flow of graphene nanoplatelet-platinum/water hybrid nanofluid with entropy generation. Issue 1 (31st December 2022) - Tausif Sk, Md; Das, Kalidas; Kundu, Prabir Kumar
Abstract : In the current research, the electrical magnetohydrodynamic (EMHD) flow of Graphene nanoplatelet doped with Platinum suspended in water as base fluid between two rotating and expanding disks is taken into deliberation. The governing equations are changed into a set of ODEs using similarity transformations and solve numerically. We also study the average entropy and average Bejan number of the system for numerous values of different factors. Graphs and diagrams are prepared to depict the effects of flow factors on the influence of electric field in various aspects of the flow. One of the significant outcomes of the analysis is that to minimise the entropy generation in the flow system due to the strong electric field, one need to a lesser magnetic field and diminish Reynolds's number for the efficiency of the system. Also with the intensifying magnetic and electrical force, heat transfer irreversibility contributes more to the entropy of the system.